FEASIBILITY OF STUDENT WORKSHEET GUIDED DISCOVERY BASED ON THE TOPIC OF ENVIRONMENTAL POLLUTION - BIDAYATUL FITRIYAH (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
One of student center learning medium is student worksheet which can help students to find and understand the concepts of the topic learning. Therefore, the researchers developed a guided discovery student worksheets based on the topic of Environmental Pollution for X grade students of SMA. This research conducted to produce a guided discovery student worksheets based on the topic of Environmental Pollution which is feasible theoretically and to describe the theoretical feasibility of guided discovery student worksheets based on the topic of Environmental Pollution. This research was done using the development of four-D model. The results showed that the resulted student worksheet guided discovery based in materials Environmental Pollution is feasible on theoretical and empirical and the student worksheet guided discovery based was feasible theoretically based on the value of student worksheet validation which was 3,67 stated as very suitable. Key words: The developing student worksheet, Environmental Pollution, guided discovery, X grade students of Senior high school.